2003
DOI: 10.1080/10437797.2003.10779148
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Web-Assisted Teaching Strategies

Abstract: This study determines which Web-assisted teaching strategies social work students from a single university experience and perceive as valuable. The results demonstrate that most faculty use email, post grades online, and give out s tuden t email addresses to the class. Students perceive email communication with the instructor and the online provision of course information as the most valuable strategies. The impact of several student characteristics on value perception is also examined, revealing varying level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 12 publications
2
43
0
Order By: Relevance
“…CSQ consisted of 21 self-report items to measure students' overall satisfaction with the online courses (Frey, Yankelov, & Faul, 2003). Students responded to each item using a seven-point Likert-type scale, ranging from completely dissatisfied (1) to completely satisfied (7) with a possible score range of 21-147.…”
Section: Csqmentioning
confidence: 99%
“…CSQ consisted of 21 self-report items to measure students' overall satisfaction with the online courses (Frey, Yankelov, & Faul, 2003). Students responded to each item using a seven-point Likert-type scale, ranging from completely dissatisfied (1) to completely satisfied (7) with a possible score range of 21-147.…”
Section: Csqmentioning
confidence: 99%
“…They also suggested that involving students in the process of getting to know each other also affects collaborative engagements. On the other hand, Frey, Faul, and Yankelov (2003) found, in their assessment of Web-assisted strategies, that students perceive e-mail communication with the instructor as the most valuable strategy; these study participants did not value highly the strategies designed to facilitate communication among students (creation of home pages, accessible e-mail addresses, and discussion groups). Young (2004) and Keefe (2003) found a high degree of interactivity and student participation to be critical components of online instruction.…”
Section: Interaction Systemsmentioning
confidence: 99%
“…Many students find email an effective way for instructors to communicate with them (Chang et al, 2015;Frey, Faul, &Yankelov, 2003;Ortiz-Rodríguez, Telg, Irani, Roberts, & Rhoades, 2005;Woods, 2002), and according to Dahlstrom (2014), 99% of institutions offering online courses use a learning management system that includes email. Nevertheless, Weinstock (2004) found that students often view email as "a form of telepathy-the instantaneous communication of an uncensored thought, often with the expectation of an immediate response" (p. 380).…”
Section: Relevant Literaturementioning
confidence: 99%